Smart card reader and electoral transparency in Nigeria : the case of 2015 general elections - Akwen, Gabriel Tyoyila; Jooji, Innocent; Ravichandran Moorthy, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Periodic elections are characteristics of contemporary democracy, because they serve as means of changing non performing representatives of the people. In Nigeria, it is difficult to ascertain whether elections have over the years served the above mentioned purpose. Elections in Nigeria have been characterized by irregularities, consequently the introduction of the Smart Card Reader to correct the abnormalities. This paper examined the effectiveness of the use of Smart Card Reader in search for electoral transparency in Nigeria, as experimented during the 2015 general elections. It relied heavily on secondly data. Using the system theory as espoused by David Easton as it theoretical foundation, the paper disclosed that, the use of smart card reader in the Nigeria’s 2015 general elections to a large extent reduced the level of electoral scam that is widely known to have characterized the Nigerian electoral system. The paper also reveals that despite the success recorded by the use of the smart card reader, there were some challenges recorded and also controversy surrounding the legality of the use of smart card reader. Based on the challenges encountered by Independent National Electoral Commission (INEC) in the use of the smart card reader, the paper recommends adequate education as the panacea for the effective use of the smart card reader in Nigeria’s subsequent elections.